Simulated overfishing and natural eutrophication promote the relative success of a non-indigenous ascidian in coral reefs at the Pacific coast of Costa Rica - Roth, Florian (2017)
Colonial ascidians of the genus Didemnum are common fouling organisms and are typically associated with degraded ecosystems and anthropogenic structures installed in the sea. In this study, however, the non-indigenous ascidian Didemnum cf. perlucidum Monniot F., 1983 was discovered in coral reef environments on the Pacific coast of Costa Rica. Its role in the succession of a benthic community and the impact on biogeochemical features (i.e. reef cementation) was assessed by deploying terracotta settlement tiles on the reef for 24 weeks. Predator exclusion in experimental plots and naturally elevated nutrient concentrations during seasonal coastal upwelling gave insights on how settlers of D. cf. perlucidum succeed under projected environmental change. Exclusion of larger predators and grazers caused an increase of D. cf. perlucidum coverage on tiles from 7 to > 80%. Due to its rapid proliferation, D. cf. perlucidum grew over calcifying reef organisms, such as barnacles, polychaetes, and crustose algae, and significantly decreased the accumulation of inorganic carbon on the settlement tiles by one order of magnitude (4.6 to 0.4 mg C cm- ²). The combination of reduced predation and eutrophication revealed negative synergistic effects on the accumulation of inorganic carbon. The opportunistic reaction of D. cf. perlucidum to environmental changes was further evident by 2-fold increased growth rates that were positively correlated (r² = 0.89) to seawater particulate organic matter (POM) concentration during coastal upwelling. These results suggest that D. cf. perlucidum is a strong spatial competitor in Eastern Tropical Pacific coral reefs that face changing environmental conditions, e.g. overfishing and eutrophication. The effects of this species on disturbed benthic communities, but also its potential role as a habitat modifier, is likely significant. Thus, a continuous monitoring of D. cf. perlucidum is recommended to better understand their effects on post-disturbance dynamics in coral reef ecosystems.